FORMULASI EKSTRAK DAUN KITOLOD (HIPOBROMA LONGIFLORA) DALAM SEDIAAN OBAT KUMUR ALAMI TERHADAP BAKTERI STREPTOCOCCUS MUTANS - Boima Situmeang; Dzulhijar; Juliandoz; Ahmad Fajar Muzakir; Agus Malik Ibrahim; Nani Yulianti; Nurhayati Bialangi; Weny JA Musa (Jurnal Crystal : Publikasi Penelitian Kimia dan Terapannya, 2025)
The kitolod plant (Hippobroma longiflora) has been demonstrated to possess antibacterial activity against Streptococcus mutans, the bacterium responsible for the development of dental caries. The objective of this study was to formulate a mouthwash preparation using kitolod leaf extract. The extract was formulated into three distinct formulations. The mouthwash was evaluated for its pH, viscosity, stability, and antibacterial activity. The antibacterial evaluation was executed in accordance with the Kirby-Bauer method. The positive control utilized in this study was 0.2% chlorhexidine. The pH test results indicated that all three formulations had a pH of 6. The viscosity test demonstrated that all formulations had a viscosity of 0.99, which is close to that of water. The antibacterial evaluation against S. mutans indicated that formulation 2 demonstrated the most pronounced antibacterial activity, exhibiting an inhibition zone measuring 3.81 mm. All three formulations exhibited stability at ambient temperature. In light of the findings from this study, it can be posited that formulation 2 possesses the potential to serve as a natural mouthwash.